Mitigasi Bencana Hidrologi Banjir Untuk Anak Usia Dini Di Tk Negeri Pembina Kampar - Wahyuni, Sri; Efastri, Sean Marta (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Events or disasters that ensue can be accomplished by early childhood, namely the attitude of alertness and disaster response, because with disasters, if children of this age are not provided mitigation education, it has an impact on their health both physically and mentally. Early childhood is different in dealing with these disasters depending on how the family supports the community and the school. Therefore, the government and schools should provide this mitigation education from an early age. Flood mitigation education in early childhood must be measured by the establishment of a program from the government in order to contribute to those who are often affected by flood disasters. Also, these educational activities in government work programs must synergize with the community so as not to throw garbage in its place, then understanding to teachers and parents related to the cleanliness of the home and school environment.